The experience at a new school education with abnormal children : Farias de Vasconcelos (1880-1939) in the context of special education - Martins, Ernesto Candeias (2017)
We approach the escolanovista Faria de Vasconcelos, in the context of modern pedagogy, the experience - School of Biérges (Belgium) and the special education with school abnormal children. Using hermeneutic and historical-descriptive analysis on his pedagogical thought and action, the goals of this study are: deepen the experience with Biérges, integrated into the ideals of the new school, which involved students for inclusion, the power of initiative, the observation, experimentation and integral culture, associating thought-action; analyze of the contributions to the education of abnormal pedagogical children and to schools, from mental and pedagogical reeducation. The theoretical framework of analysis is based on the works of Vasconcelos. Teaching always included the practical application, the learning by inquiry, problem solving and the working doing, developing the basic dimensions of the child: physical, intellectual, moral and civic cooperation. The special attention given to abnormal, which at the time had no special school, was a huge contribution to special education, conducting psych pedagogical examinations, diagnostics and interventions, which provided a useful guidance to schools and teachers. Much of what the escolanovista made has encouraged schools at that time and formed free, productive, citizens with a general culture and professional formation. The proposals of Vasconcelos fit some guidelines of special education and psychological support